Our Early Term Pars Plana Vitrectomy Results - Yılmaz, Turgut; Köhle, Ülkü; Kükner, Şahap; Aydemir, Orhan (Fırat University, 2003)
Aim: We evaluated the etiology, peroperative and postoperative complications of the cases who underwent pars plana vitrectomy in our clinic. Material and method: Twenty patients who were operated and followed between November 2001- November 2002 included in this study. Twenty eyes of 20 patients were included in this study. The mean age of the patients was 61 (3-76) years old, of them, 9 (45%) were male, and 11 (55%) were female. The mean follow up period was 6 months (range 1-11 months). Results: Diagnoses were vitreous hemorrhage in 12 (60%), endophtalmitis in 3 (15%), asteroid hyalozis in 1 (5%), dislocated intraocular lens in 1 (5%), nucleus drop in 3 (15%) patients. Peroperative complications were iatrogenic retinal tears in 2 (10%), nucleus drop in 1 (5%), minimal vitreous hemorrhage in 1 (5%), corneal epithelial defects in 3 (15%) patients. Postoperative complications were corneal edema in 5 (25%), fibrinous reaction in 4 (20%), hypotony in 3 (15%), increased intraocular pressure in 3 (15%), retinal detachment in 2 (10%), vitreous hemorrhage in 2 (10%) and cataract in 1 (5%) patients. Conclusion: Etiology, peroperative and postoperative complications of PPV are affects of operations. We consider that we will obtain more successful results when our surgical experiences are getting improve.

Amaç: Kliniğimizde pars plana vitrektomi yapılan olguların etyolojileri, peroperatif ve postoperatif komplikasyonları değerlendirildi. Gereç ve yöntem: Kliniğimizde Kasım 2001-Kasım 2002 tarihleri arasında pars plana vitrektomi (PPV) uygulanan 20 olgunun 20 gözü çalışma kapsamına alınmıştır. Olguların yaş ortalaması 61±10.25 (3-76) olup, 9 (%45) olgu erkek, 11 (%55) olgu bayan hastalardan oluşmaktadır. Ortalama takip süresi 6± 2.8 (1-11) aydır. Bulgular: Ameliyat endikasyonu etyolojilerine göre 12 olguda (%60) vitreus hemorajisi, 3 olguda (%15) endoftalmitis, 1 olguda (%5) asteroid hyalozis, 1 olguda (%5) göz içi lens (GIL) dislokasyonu, 3 olguda (%15) vitreus içine nukleus düşmesi olarak saptandı. Ameliyat esnasında olguların 2 sinde (%10) iyatrojenik retina yırtığı, 1 olguda (%5) vitreus içine nukleus düşmesi, 2 olguda (%10) minimal vitreus hemorajisi ve 3 olguda (%15) ise kornea epitel defekti görülmüştür. Ameliyat sonrası 5 olguda (%25) kornea ödemi, 4 olguda (%20) fibrin reaksiyonu, 3 olguda (%15) göz içi basınç artışı, 3 olguda (%15) hipotoni, 2 olguda (%10) retina dekolmanı, 2 olguda (%10) vitreus hemorajisi ve 1 olguda (%5) ise katarakt görülmüştür. Sonuç: PPV ameliyatlarında başarıyı etyoloji, peroperatif ve postoperatif komplikasyonlar belirlemektedir. Cerrahi tecrübemiz geliştikçe başarı oranlarımızın artacağı kanaatindeyiz.
Pars Plana Vitrektomi Erken Dönem Sonuçlarımız